2018
DOI: 10.1038/s41598-018-32376-4
|View full text |Cite
|
Sign up to set email alerts
|

Simvastatin Protects Cardiomyocytes Against Endotoxin-induced Apoptosis and Up-regulates Survivin/NF-κB/p65 Expression

Abstract: This study is aimed to investigate whether simvastatin induces cardiomyocytes survival signaling in endotoxin (lipopolysaccharide, LSP)-induced myocardial injury, and if so, further to determine a role of survivin in simvastatin-anti-apoptotic effect. Wistar rats were pretreated with simvastatin (10–40 mg/kg po) before a single non-lethal dose of LPS. In myocardial tissue, LPS induced structural disorganization of myofibrils with significant inflammatory infiltrate (cardiac damage score, CDS = 3.87 ± 0.51, p <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 31 publications
5
38
0
Order By: Relevance
“…Here, we showed that one of the potential protective mechanisms of simvastatin against AKI is blockade of renal tubular cell apoptosis, confirmed by reduced cytochrome C and cleaved caspase-3 expression and corresponding DNA fragmentation. Interestingly, results of antiapoptotic actions of simvastatin through inhibition of pro-apoptotic Bim/Bax and effectors caspases have been well documented in hepatocytes and lymphocytes, and cardiomyocyte in other’s and our previous studies [ 20 , 21 , 28 , 29 ].…”
Section: Discussionmentioning
confidence: 53%
See 4 more Smart Citations
“…Here, we showed that one of the potential protective mechanisms of simvastatin against AKI is blockade of renal tubular cell apoptosis, confirmed by reduced cytochrome C and cleaved caspase-3 expression and corresponding DNA fragmentation. Interestingly, results of antiapoptotic actions of simvastatin through inhibition of pro-apoptotic Bim/Bax and effectors caspases have been well documented in hepatocytes and lymphocytes, and cardiomyocyte in other’s and our previous studies [ 20 , 21 , 28 , 29 ].…”
Section: Discussionmentioning
confidence: 53%
“…Further, simvastatin induced intense and dose-dependent expression of survivin in the tubular epithelium that is inversely correlated with cytochrome C and cleaved caspase-3 respectively, and indicates its evident anti-apoptotic effects. Because our previous studies indicated an important role of survivin/NF-κB/p65 pathway activation in cytoprotection against LPS-injury [ 20 , 21 ], similar to Wilson et al [ 37 ], in CLP-induced cardiomyopathy, we hypothesized that simvastatin has significant cell-protective effects in septic AKI but not only by inhibiting of apoptotic cell death but through induction of the important intracellular survival pathways in renal tubular epithelium.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations